Pengenalan Teori Permainan dan Statistika Dasar ke Siswa SMAN 1 Selong dengan Pendekatan MSJ - Ayes Malona Siboro; Bulqis Nebulla Syechah; Dina Eka Putri; Fariz Maulana; I Gede Adhitya Wisnu Wardhana; Irwansyah Irwansyah; Lailia Awalushaumi; Lalu Hasan Ghoffari; Lalu Riski Wirendra Putra; Muhammad Naoval Husni; Nur Asmita Purnamasari; Nuzla Af'idatur Robbaniyyah; Salwa Salwa; Qurratul Aini; Zata Yumni Awanis (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2023)
The community engagement activity carried out by the teaching team from the Mathematics Program of the Faculty of Mathematics and Natural Sciences at Universitas Mataram to SMAN 1 Selong has successfully introduced students to the importance of statistics and game theory in decision-making. Through stories and real-life cases, students are encouraged to consider factors such as averages and standard deviations in making informed decisions. They also learn about the story of John Nash, who discovered game theory, and compare it to the economic principles of Adam Smith. Students realize that collective interests can lead to better outcomes than personal interests. In the case of The Prisoner's Dilemma, students also see the importance of game theory in the context of collective decision-making. Overall, this activity helps students understand the importance of statistics and game theory in the decision-making process.